Development and investigation of thermal insulation from hemp-polylactide fibres. Issue 1 (2nd January 2016) - Stapulionienė, Rūta; Tupčiauskas, Ramūnas; Vaitkus, Saulius; Vėjelis, Sigitas
Abstract: In the last two decades intensive grow of industry of building materials from renewable resources is observed. Such situation is related to some aspects: global warming, environmental pollution, impact on human health, environmental impact of materials at their end-of-life. In current study development of thermal insulation materials from hemp and polylactide fibres are analysed. While main parameter for thermal insulation materials is thermal conductivity, rational density of composite 40 kg/m 3 was chosen. For experiments 11 compositions were prepared. One composition was prepared just with hemp and polylactide fibres, five compositions with different amount of hydrophobic agent and 5 compositions with different amount of fire retardant. Experimentally thermal conductivity, sound absorption coefficient, short-term water absorption, fire resistance, water vapour transfer properties and compressive strength were determined. Rational amount of hydrophobic agent and fire retardants was chosen.